Different Donor–Acceptor Interactions of Carbene Ligands in Heteroleptic Divalent Group 14 Compounds, LEL′ (E=C–Sn; L=N‐Heterocyclic Carbene; L′=Cyclic Alkyl(Amino) Carbene). Issue 15 (16th February 2018) - Purushothaman, Indu; De, Susmita; Parameswaran, Pattiyil
Abstract: The electronic structure and reactivity of heteroleptic divalent group 14 compounds, 1E (E=C–Sn) with NHC and cAAC ligands have been studied at the BP86/TZ2P level of theory and compared with homoleptic group 14 compounds. The EDA–NOCV (energy decomposition analysis–natural orbitals for chemical valence) analysis indicates that the interaction between the two carbene ligands and the central C‐atom in1C can be best represented as one 3c–2e electron sharing σ‐bond and one 3c–2e donor–acceptor σ‐bond. There exists an electron sharing interaction between the π‐type orbital on the central C‐atom and the C−N π* orbital of cAAC and a π‐back‐donation from the σ‐type lone pair on the central C‐atom to the π*‐MO of NHC. This bonding description is equivalent to the localized bonding representation, where the central C‐atom forms two electron sharing bonds and two donor‐acceptor bonds with cAAC and NHC ligands. However, the bonding between the carbene ligands and the heavier group 14 element can be best represented as two 2c–2e donor–acceptor σ‐bonds and a π‐back‐donation from group 14 element to C−N π* orbital of cAAC. This bonding description is well supported by the geometrical and Natural Bond Orbital (NBO) analyses. Hence, 1C can be best described as a carbene and the heavier analogues can be best described as tetrylones. However, the high first (287.6–274.3 kcal mol −1 ) and second proton affinities (162.0–158.5 kcal mol −1 ) suggest that1E (E=C–Sn) behave as tetrylones. Abstract : Carbenes : The electronic structure and reactivity of heteroleptic divalent group 14 compounds, 1E (E=C–Sn) with NHC and cAAC ligands have been studied at the BP86/TZ2P level of theory and compared with homoleptic group 14 compounds.